Smart City Optimization Through AI-Driven BI Systems: Multimodal Data Fusion for Urban Mobility and Energy Efficiency - Akhtar, Masroor (Journal of Research in Science and Engineering, 2025)
As cities grow increasingly complex, the integration of Artificial Intelligence (AI) and Business Intelligence (BI) plays a pivotal role in shaping urban environments, optimizing resource management, and enhancing citizens' quality of life. This paper explores the critical role of AI and BI in creating smart cities, offering data-driven solutions that impact transportation, energy consumption, public safety, and healthcare. Real-time case studies from cities around the globe demonstrate how AI and BI have been successfully implemented, transforming traditional urban services into efficient, intelligent systems. The significance of this paper lies in addressing the challenges and potential of AI and BI, encouraging the development of sustainable and smart urban systems.